The types of audit reports in pension funds in Brazil - da Silva Neto, Geraldo Joaquim (2019)
The purpose of this article was to analyze the reports issued by external auditors in Brazil's pension funds. For this, a documentary research was conducted in the audit reports of the years 2015 and 2016 of the Closed Entities of Complementary Pension Plans (EFPC) sponsored by Energy companies and Banks listed in B3, together with the entity sponsored by “Caixa Econômica Federal”. The results of this study highlighted a compliance of audit reports with technical accounting standards and that EFPCs have financial statements in accordance with the regulatory body, a minority presented paragraph of emphasis and qualified opinion. In addition, the study concludes that the reports analyzed are mostly the same in terms of structure or content.